Perceived progress variability and entrepreneurial effort intensity : the moderating role of venture goal commitment - Uy, Marilyn A. (2014)
Drawing on entrepreneurial motivation and goal striving literatures, we examined the dynamic relationship between momentary perceived progress, or an ongoing sense of how one is doing in the pursuit of one’s venture goal, and entrepreneurial effort intensity among early-stage entrepreneurs who are based in business incubators. We also examined how perceived progress variability over time predicted entrepreneurial effort intensity, and whether venture goal commitment moderated this link. Experience-sampling data collected from over one hundred early-stage entrepreneurs indicated that perceived progress predicted greater effort intensity. Moreover, perceived progress variability over time negatively predicted entrepreneurial effort intensity, and venture goal commitment attenuated this negative relationship. Theoretical and practical implications of our study to entrepreneurial motivation and goal striving research are discussed.